Ptgds downregulation protect vestibular hair cells from aminoglycoside-induced vestibulotoxicity - Chen Chen; Zhimin Zhao; Jinghong Han; Yue Zhang; Guohui Nie (PLoS ONE, 2025)
The clinical use of aminoglycosides often results in injury to vestibular hair cells and subsequent vestibular dysfunction. Thus, clarifying the targets and mechanisms underlying aminoglycoside-mediated damage is of urgent importance. Prostaglandin D2 synthase (Ptgds) is a glycoprotein that plays dual roles in lipid transport regulation and prostaglandin metabolism. However, the role of Ptgds in aminoglycoside-induced vestibular dysfunction remains unclear. This study aimed to explore the function of Ptgds in the utricle and HEI-OC1 cells. Neomycin injury induced high levels of Ptgds expression in utricle explants. Moreover, Ptgds knockdown protected against neomycin injury by enhancing cellular proliferation and viability while suppressing reactive oxygen species production, inflammation, and apoptosis. These findings suggest that Ptgds may serve as a novel therapeutic target for treating vestibular dysfunction caused by aminoglycoside-induced damage.